Green grinding of ultra-high molecular weight polyethylene using glass fiber reinforced highly porous 3D-printed metal bond grinding wheel - Mohsen Barmouz; Felix Steinhäuser; Bahman Azarhoushang (Results in Materials)
Addressing global concerns regarding environmentally unfriendly production methods that pose significant health risks to humans and the environment, this research study introduces a highly porous, additively manufactured metal bond grinding wheel reinforced with glass fiber. This innovative wheel is designed to facilitate green grinding processes on ultra-high molecular weight polyethylene. Thanks to its highly porous structure, the printed grinding wheel does not require coolant fluid during dressing and grinding experiments. A comprehensive series of grinding experiments was conducted to evaluate the performance of the printed grinding wheel and investigate the impact of various grinding parameters. The results indicated that the printed wheel has significant potential for dry grinding. Optimal grinding parameters led to marked improvements in grinding performance, including a reduction in surface roughness by up to 3 times, a decrease in grinding force by up to 3.5 times, higher dimensional accuracy, an improved force ratio by up to 3 times, and reduced energy consumption by up to 4 times. Additionally, observations using optical and laser microscopy revealed intensified wheel loading and notable modifications in the surface texture of the ground parts when different grinding parameters were applied.